Cybernetic Diagrams: Design Strategies for an Open Game. (December 2014) - Veloso, Pedro L.A.
This paper investigates the use of diagrams related to cybernetics and information theory in experimental design practices in the 1960s and 1970s. Those diagrams are investigated in light of Vilém Flusser's concept of game, which mediates the modus operandi of computers and possible strategies for design based on distributed cognition. The research adopts the interpretative method to analyze the diagram proposed by cyberneticist Gordon Pask for Fun Palace, the diagrams produced by utopian architect Yona Friedman in the conceptual description of the Flatwriter program and Christopher Alexander's diagrams for his theories of Synthesis of Form and Pattern Language. In the end, it establishes a brief parallel between current debates of computational design with the cybernetic diagrams, highlighting differences in their approach to complexity and design knowledge.